2005
DOI: 10.1099/mic.0.27629-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the β-lactamases of Mycobacterium tuberculosis and Mycobacterium smegmatis and susceptibility to β-lactam antibiotics

Abstract: Mycobacteria produce β-lactamases and are intrinsically resistant to β-lactam antibiotics. In addition to the β-lactamases, cell envelope permeability and variations in certain peptidoglycan biosynthetic enzymes are believed to contribute to β-lactam resistance in these organisms. To allow the study of these additional mechanisms, mutants of the major β-lactamases, BlaC and BlaS, were generated in the pathogenic Mycobacterium tuberculosis strain H37Rv and the model organism Mycobacterium smegmatis strain PM274… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
178
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(190 citation statements)
references
References 39 publications
10
178
1
1
Order By: Relevance
“…Interestingly, failure to secrete BlaS confers ampicillin susceptibility upon strains with tatA, tatB, or tatC mutations. This is consistent with the observation that deletion of blaS confers ampicillin susceptibility (14), although M. smegmatis contains several lactamases (www.tigr.org.tdb /ofmg/). We analyzed the genome of M. smegmatis with TATFIND (11) and identified 49 putative TAT substrates, which represent approximately 0.7% of the encoded proteins.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, failure to secrete BlaS confers ampicillin susceptibility upon strains with tatA, tatB, or tatC mutations. This is consistent with the observation that deletion of blaS confers ampicillin susceptibility (14), although M. smegmatis contains several lactamases (www.tigr.org.tdb /ofmg/). We analyzed the genome of M. smegmatis with TATFIND (11) and identified 49 putative TAT substrates, which represent approximately 0.7% of the encoded proteins.…”
Section: Discussionsupporting
confidence: 78%
“…We previously showed that the mutants have an increased susceptibility to most ␤-lactam antibiotics, particularly the penicillins. However, there is still a basal level of resistance in the mutants to certain penicillins, and the susceptibilities of the mutants to some cephalosporin-based ␤-lactams are essentially the same as those of the wild types (17). We found a minor cephalosporinase, BlaE, in M. smegmatis but showed that its contribution to ␤-lactam resistance is minimal (17).…”
mentioning
confidence: 74%
“…To eliminate this problem, our laboratory has constructed mutants of M. tuberculosis and M. smegmatis with deletions of the major ␤-lactamase genes, blaC and blaS, respectively (17). We previously showed that the mutants have an increased susceptibility to most ␤-lactam antibiotics, particularly the penicillins.…”
mentioning
confidence: 99%
“…A mycobacterial AmpG homologue has not yet been identified and characterized, but some transport of the PG material back into the cytosol would be needed. It should be noted that mycobacteria do have ␤-lactamases, enzymes associated with cell wall monitoring and remodeling (136,137,271,434).…”
Section: Do Mycobacteria Recycle Cell Wall Material?mentioning
confidence: 99%